Report of a giant titanosaur sauropod from the Upper Cretaceous of Neuquén Province, Argentina. (June 2021) - Otero, Alejandro; Carballido, José L.; Salgado, Leonardo; Canudo, José Ignacio; Garrido, Alberto C.
Abstract: One of the most fascinating research topics in the field of sauropod dinosaurs is the evolution of gigantism. In the particular case of Titanosauria, the record of multi-ton species (those exceeding 40 tons) comes mainly from Patagonia. The record of super-sized titanosaur sauropods has traditionally been extremely fragmentary, although recent discoveries of more complete taxa have revealed significant anatomical information previously unavailable due to preservation biases. In this contribution we present a giant titanosaur sauropod from the Candeleros Formation (Cenomanian, circa 98 Ma) of Neuquén Province, composed of an articulated sequence of 20 most anterior plus 4 posterior caudal vertebrae and several appendicular bones. This specimen clearly proves the presence of a second taxon from Candeleros Formation, in addition to Andesaurus, and is here considered one of the largest sauropods ever found, probably exceeding Patagotitan in size. While anatomical analysis does not currently allow us to regard it as a new species, the morphological disparity and the lack of equivalent elements with respect to coeval taxa also prevent us from assigning this new material to already known genera. A preliminary phylogenetic analysis places this new specimen at the base of the clade leading to Lognkosauria, in a polytomy with Bonitasaura . The specimen here reported strongly suggests the co-existence of the largest and middle-sized titanosaurs with small-sized rebbachisaurids at the beginning of the Late Cretaceous in Neuquén Province, indicating putative niche partitioning. This set of extremely large taxa from Patagonia has contributed to a better understanding of the phylogenetic relationships of titanosaurs, revealing the existence of a previously unknown lineage and shedding new light on body mass evolution.